2007
DOI: 10.1097/hjh.0b013e328013e7dd
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation endproduct crosslink breaker (alagebrium) improves endothelial function in patients with isolated systolic hypertension

Abstract: Alagebrium enhances peripheral artery endothelial function and improves overall impedance matching. Improved endothelial function correlates better with reduced vascular fibrosis and inflammation markers than with vessel distensibility. AGE-crosslink breakers may reduce cardiovascular risk in older adults by reduced central arterial stiffness and vascular remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
128
0
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(139 citation statements)
references
References 48 publications
(62 reference statements)
4
128
0
7
Order By: Relevance
“…Furthermore, administration of AGE crosslink breaker (ALT-711) to patients with hypertension was associated with a concurrent reduction in AGEs, improved endothelial function and reduced arterial stiffness and pulse pressure [29]. These data bolster the evidence of the involvement of AGEs in hypertension as well as arterial stiffening [29,[59][60][61]. We showed for the first time that higher circulating levels of CML were associated with lower diastolic blood pressure and higher pulse pressure in young healthy normotensive individuals.…”
Section: Discussionsupporting
confidence: 66%
“…Furthermore, administration of AGE crosslink breaker (ALT-711) to patients with hypertension was associated with a concurrent reduction in AGEs, improved endothelial function and reduced arterial stiffness and pulse pressure [29]. These data bolster the evidence of the involvement of AGEs in hypertension as well as arterial stiffening [29,[59][60][61]. We showed for the first time that higher circulating levels of CML were associated with lower diastolic blood pressure and higher pulse pressure in young healthy normotensive individuals.…”
Section: Discussionsupporting
confidence: 66%
“…The prevention or decrease of glycation and glycation-induced tissue damage could be possible therapeutic strategies for the treatment of diabetic neuropathy [39,40]. Recent clinical studies have shown that AGE breakers, including ALT-711 and alagebrium, may be able to decrease the adverse vascular effects of glycation with few side effects [41][42][43], although no benefits have been demonstrated in the area of neuropathy. The inhibition of pathological responses mediated by AGEs may have therapeutic potential for diabetic neuropathy, although the RAGE-mediated molecular mechanisms need to be explored in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Az AGE keresztkötése-it törő alagebrium fokozza a perifériás artériák endotheljének a működését, mérsékeli az ED-t [69], a teljes impedanciát javítja, valamint csökkenti a centrális artériák merevségét és az erek átépülését.…”
Section: Alagebriumunclassified